The Influence of ROA, ROE, and NPM on Company Value with Dividend Policy as a Mediation Variable - Mariana; Suryadi, Edy (INOVASI: Jurnal Ekonomi, Keuangan, dan Manajemen, 2024)
This research aims to determine the effect of ROA, ROE, and NPM on Company Value (PBV) with Dividend Policy as mediation in raw goods companies on the Indonesia Stock Exchange (BEI) for the 2020-2022 period. The data collection method is documentation study. Samples were taken using the purposive sampling method. A sample of 49 companies was obtained from a population of 96 companies registered in the automotive subsector over a 3 year period (2020-2022). This research data uses multiple linear regression analysis. The results of hypothesis testing prove that NPM has an influence on dividend policy, but ROA and ROE have no influence on dividend policy. ROE and NPM have an influence on company value, but ROA and dividend policy have no influence on company value. Dividend policy (DPR) can mediate the effect of ROA on company value but cannot mediate the effect of ROE and NPM on company value.